Performance of an emulsion telescope for gamma-ray observations in the GRAINE2018 balloon-borne experiment. (17th November 2021) - Nakamura, Yuya; Aoki, Shigeki; Iyono, Atsushi; Karasuno, Ayaka; Kodama, Kohichi; Komatani, Ryosuke; Komatsu, Masahiro; Komiyama, Masahiro; Kuretsubo, Kenji; Marushima, Toshitsugu; Matsuda, Syota; Morishima, Kunihiro; et al.
Abstract: The Gamma-Ray Astro-Imager with Nuclear Emulsion (GRAINE) project is aimed at the precise observation of astronomical gamma-ray sources in the energy range of 10 MeV–100 GeV using a balloon-borne telescope utilizing a nuclear emulsion, which can help realize precise imaging with high angular resolution (1.0 ○ at 100 MeV), polarization sensitivity, and large aperture area (10 m 2 ). In 2018, the third balloon experiment was carried out as a demonstration of the detection of the brightest known astronomical gamma-ray source, the Vela pulsar, with an aperture area of 0.38 m 2 . In these data, some gamma rays were produced by the π 0 → 2γ decay, which was caused by the hadronic interactions of cosmic rays in the detector. These could be used to calibrate the reconstructed angle, energy, and so on. In this study, we establish a method of searching for hadronic interactions and concomitant gamma rays with high statistics and purity. Our analysis indicates that the performance of our detector for gamma rays is as expected in wide incidence angle and energy ranges. We plan to commence scientific observations using the proposed system with the verified high angular resolution and largest aperture area in 2022 or later.